In good company - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Spore moves all sorts of people in all sorts of ways, says Simon Digdjag Antcha, a rural communicator in Moundou, Chad, who wrote 'After receiving Spore, and re-reading it, I hand it to my friends and relations to read. Several people have got so...